Pengembangan Website SpendNote sebagai Sistem Pencatatan Pengeluaran Keuangan Menggunakan Framework Laravel - Rifda Triani Mutmainah; Syarif Hidayatulloh (Jurnal Teknik dan Science, 2026)
The rapid development of information technology has encouraged the use of web-based applications in various aspects of daily life, including personal financial management. However, many individuals still do not consistently record their financial transactions due to limitations of existing applications, such as complex interfaces, dependence on paid features, and limited accessibility. This study aims to develop the SpendNote Website as a web-based financial expense recording system that is easy to use, free of charge, and capable of presenting financial information in a clear and structured manner. The research method employed is applied research, consisting of problem identification, system requirements analysis, system design, implementation, testing, and evaluation. The SpendNote Website was developed using the Laravel framework with the Model–View–Controller (MVC) architecture. The results show that SpendNote is able to record income and expenses, display financial summaries, provide transaction history, period-based filtering, and data visualization in the form of graphs and charts. Functional testing indicates that all system features operate properly and meet user requirements. Therefore, the SpendNote Website can serve as a practical and effective solution to support systematic and sustainable personal financial management.